2021
DOI: 10.1155/2021/5511127
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion and Mechanical Properties of the Fe‐W‐Wo2 and Fe‐Mo‐MoO2 Nanocomposites

Abstract: Analyzing of composition electrolytic coatings’ application for the metal surface protection is considered. It is established that using different components for coatings’ modification gives possibility to obtain surfaces with expanding exploitation properties, in particular, with improved wearing and anticorrosion resistance. The new approach for protecting details which are made from cast irons by obtaining two kinds of composition coatings from binary alloys iron-molybdenum and iron-tungsten is proposed. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Studies of the pitting resistance of AISI 304 and AISI 321 steels showed that it mainly depends on the parameters of model circulating waters (x i , x 2 ),the content in them Cr within the standard. At the same time, the results of the analysis (Table 3, № 5) of the mathematical model ( 1) are harmonized with the data of works [16,[31][32][33][34][35] CPT increases by 7.4°C with an increase in the Cr content in steels from 17.1 to 18.3 mass% (Table 1). The pitting resistance of steels and alloys alloyed with Cr is associated with oxide films formed by Cr with O [36 -40].…”
Section: Research Results and Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Studies of the pitting resistance of AISI 304 and AISI 321 steels showed that it mainly depends on the parameters of model circulating waters (x i , x 2 ),the content in them Cr within the standard. At the same time, the results of the analysis (Table 3, № 5) of the mathematical model ( 1) are harmonized with the data of works [16,[31][32][33][34][35] CPT increases by 7.4°C with an increase in the Cr content in steels from 17.1 to 18.3 mass% (Table 1). The pitting resistance of steels and alloys alloyed with Cr is associated with oxide films formed by Cr with O [36 -40].…”
Section: Research Results and Discussionmentioning
confidence: 94%
“…The pitting resistance of steels and alloys alloyed with Cr is associated with oxide films formed by Cr with O [36 -40]. In addition, this element affects the solid-phase diffusion of Cr atoms to the surface of metastable pits and promotes their repassivation [33][34][35]. There is an evidence that Cr [41] increase the solubility of nitrogen in corrosionresistant steels, and, consequently, their pitting resistance.…”
Section: Research Results and Discussionmentioning
confidence: 99%
“…Surface treatments are critical to eliminating or minimizing material losses due to wear and corrosion in steel. In addition, different properties of steel such as oxidation resistance, mechanical and electrical-electronic properties, and thermal properties can be improved by surface treatments [4]. Anti-corrosion and anti-wear surface treatments applied to steel materials are listed in Figure 2.…”
Section: Preventive Surface Treatments Against Wear and Corrosionmentioning
confidence: 99%